Proton Spectra for the Interplanetary Space Derived From Different Environmental Models - Klein, E. M.; Sznajder, M.; Seefeldt, P. (Frontiers in Space Technologies, 2022)
Knowledge about the space radiation environment is crucial for the design and selection of materials and components used for space applications. This environment is characterized not only by the Sun’s electromagnetic radiation but also by charged particles categorized into solar wind, solar energetic particles (SEP) and galactic cosmic rays (GCR). Especially for material engineering and qualification testing, differential and integral spectra for particle energies ranging from keVs to GeVs are required. Up to now, a wide variety of models is available, whereas it is difficult to keep the overview. Although, e.g., the ecss standard includes instructions on how to investigate particle radiation, it does not provide an overall view. This paper shall support those in need of a comprehensive overview and provide comprehensive information about proton radiation spectra that can potentially be of use for space engineering tasks ranging from mission analysis to material and component design as well as qualification testing. The publicly accessible platforms OLTARIS, SPENVIS and OMERE were examined for available proton spectra to be used. Exemplary, the particle radiation of solar cycle 23 is considered, which comprehends the years 1996 to 2008. A common drawback of the available models is their restriction to the MeV-range. Particularly when materials are directly exposed to the space environment, low energetic particles, specifically, the keV-range, are of high interest, since these particle transfer all their energy to the material. Therefore, additional data sources were used in order to include the usually neglected low energy protons into the derived spectrum. The data was transferred to common set of units and eventually could be compared and merged together. This includes a comparison of the most common models, incorporating data foundation, applicability and accessibility. As a result, extensive and continues spectra are fitted that take all different models with its different energies and fluxes into account. Each covered year is represented by a fitted spectrum including confidence level as applicable. For solar active and quite times spectra are provided.